2022
DOI: 10.1101/2022.06.28.22276983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes of laboratory-confirmed SARS-CoV-2 infection during resurgence driven by Omicron lineages BA.4 and BA.5 compared with previous waves in the Western Cape Province, South Africa

Abstract: ObjectiveWe aimed to compare clinical severity of Omicron BA.4/BA.5 infection with BA.1 and earlier variant infections among laboratory-confirmed SARS-CoV-2 cases in the Western Cape, South Africa, using timing of infection to infer the lineage/variant causing infection.MethodsWe included public sector patients aged ≥20 years with laboratory-confirmed COVID-19 between 1-21 May 2022 (BA.4/BA.5 wave) and equivalent prior wave periods. We compared the risk between waves of (i) death and (ii) severe hospitalizatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 20 publications
4
33
1
Order By: Relevance
“…While some South African studies have suggested that Omicron BA.4 and BA.5 had similar disease severity to Omicron BA.1 and BA.2 (16,21), our data indicate a lower risk of mortality in the Omicron BA.4/BA.5 wave compared to the Omicron BA.1/BA.2 wave. Immunological observations from South Africa point to considerable immune escape of Omicron BA.4 and BA.5 from Omicron BA.1 elicited immunity, but much less so in those with vaccination (15).…”
Section: Discussioncontrasting
confidence: 84%
“…While some South African studies have suggested that Omicron BA.4 and BA.5 had similar disease severity to Omicron BA.1 and BA.2 (16,21), our data indicate a lower risk of mortality in the Omicron BA.4/BA.5 wave compared to the Omicron BA.1/BA.2 wave. Immunological observations from South Africa point to considerable immune escape of Omicron BA.4 and BA.5 from Omicron BA.1 elicited immunity, but much less so in those with vaccination (15).…”
Section: Discussioncontrasting
confidence: 84%
“…Recent studies from the UK 11 and Denmark (preprint) 8 reported no differences in odds of vaccination between BA.5 and BA.2 cases. A severity assessment from South Africa (preprint) reported no differences in risk of severe hospitalization/death during BA.4/5 wave compared to BA.1 wave 12 . In contrast, recent study from Denmark reported higher odds of hospitalization among BA.5 cases compared to BA.2, even among those vaccinated with a booster dose 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study reveals an ebbing off in the in-hospital deaths during the last months which were driven by the latter variants of Omicron. Omicron marked a change in the SARS-CoV-2 epidemic curve, clinical profile, and deaths in South Africa (33) Davies et al showed similar patterns in the Western Cape province (9).…”
Section: Discussionmentioning
confidence: 95%
“…This was first noted in December 2019 in Wuhan, China, where a cluster of patients with pneumonia of unknown cause was identified (1)(2)(3) South Africa recorded its first confirmed COVID-19 case in March 2020 and the government took decisive action to mitigate the spread of the disease through implementing a state of disaster and then adjusted mitigation levels (4) The first wave (peak) of COVID-19 infections occurred in July 2020 in South Africa and four more waves followed (5)(6)(7)(8). The most recent waves dominated by Omicron sub-variants have been less severe due to high levels of immunity from vaccination and prior infection in South Africa (5,9,10). As of March 2022, there has been more than 3.6 million confirmed COVID-19 cases and 100 000 confirmed deaths in South Africa, making it the most affected country in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%